Counter-piracy law in practice : an ethnography of international security governance - Larsen, Jessica, 1982- (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2023)
"This book is a socio-legal study of counter-piracy. It takes as its case the law enforcement efforts after 2008 to suppress piracy off the coast of Somalia. Through ethnographic fieldwork, the book invites the reader onto a Danish warship patrolling the western Indian Ocean for piracy incidents and into the courtroom in Seychelles, where more than 150 suspects were prosecuted. The aim is to understand how counter-piracy worked in practice. The book uses assemblage theory to approach law as a social process and places emphasis on studying empirical enforcement practices over analysing legal provisions. This supplements existing scholarship on the legal aspects of counter-piracy. Scholarship has mainly examined applicable law governing counter-piracy. This book steps into the field to examine applied law. Its methodology renders visible areas of legal ambiguity and identifies practices which suggests impunity and questions legal certainty. It thus contributes with new policy-relevant knowledge for international security governance. The relevance is one of urgency. Counter-piracy off Somalia has served as a governance paradigm, which is replicated in other maritime domains. Consideration of the implications for policy is therefore needed. The book will be of interest to policy-makers, security practitioners and scholars, who share a methodological commitment to practice"--
The law : legal debates on counter-piracy in the western Indian Ocean -- The approach : 'following the law' in practice -- The warship : maritime policing in the Indian Ocean -- The courtroom : piracy prosecution in Seychelles -- The implications : socio-legal conclusions on counter-piracy.
OCLC-licensed vendor bibliographic record.
Keywords: Piracy (International law); Piracy -- Prevention -- Law and legislation; Maritime terrorism -- Law and legislation; LAW / International; LAW / Maritime; POLITICAL SCIENCE / International Relations / General